Are Endophytic Bacteria an Option for Increasing Heavy Metal Tolerance of Plants? A Meta-Analysis of the Effect Size - Franco-Franklin, Valeria; Moreno-Riascos, Sandra; Ghneim-Herrera, Thaura (Frontiers in Environmental Science, 2021)
Plant endophytic bacteria have received special attention in recent decades for their ability to improve plant response to multiple stresses. A positive effect of endophytes on plant´s ability to cope with drought, salinity, nitrogen deficiency, and pathogens has already been demonstrated in numerous studies, and recently this evidence was consolidated in a meta-analysis of published data. Endophytic bacteria have also been implicated in increasing resistance to heavy metals in plants; despite the important biotechnological applications of such effect in heavy metal bioremediation and agriculture, efforts to systematically analyze studies in this field have been limited. In this study, we address this task with the objective of establishing whether the findings made for other types of stresses extend to the response to heavy metals. Specifically, we seek to establish if plant inoculation with plant-growth-promoting endophytic bacteria has an impact on their tolerance to heavy metal stress. We carried out a meta-analysis of the effect size of inoculation with endophytic bacteria on the host plant biomass in response to heavy metal stress (aluminum, arsenic, cadmium, copper, chromium, manganese, nickel, lead, and zinc), which included twenty-seven (from seventy-six published in the last ten years) studies under controlled conditions that evaluated nineteen host plants and twenty bacterial genera. Our results suggest that endophytic bacteria increase the biomass production of host plants subjected to different heavy metals, indicating their effectiveness in protecting plants from a wide range of metal toxicities. Stress mitigation by the bacteria was similar among the different plant groups with the exception of non-accumulating plants that benefit most from the symbiotic association. Host identity and heavy metal concentration seem to influence the effect of the bacteria. Our analysis revealed that bacterial consortia provide the greatest benefit although the most common biotechnological applications are not directed towards them, and support the value of endophytic bacteria as an alternative to mitigate heavy metal stress in a wide variety of hosts.